Pendampingan Ektrakurikuler Ludruk Sebagai Kegiatan Pendidikan Non Formal dalam Pembinaan Siswa di SDN Ketapang Kuning Jombang - Nusantara, Widya; Wulandari, Anita Jaya; Widodo, Rika Angelina; Rahayu, Shinta (Program Studi Ilmu Hukum Fakultas Hukum Universitas Kuningan, 2022)
Ludruk is a traditional art form originating from East Java. Ludruk is included in one of the traditional drama arts which is played or performed by several people who are members of an art group or group. One of them is an extracurricular activity held at SDN Ketapang Kuning which has a new extracurricular activity that is quite different from other extracurricular activities, namely ludruk extracurricular because it collaborates with ludruk art under the leadership of Mr. Didik Purwanto as the school builder. extracurricular ludruk and owner of the legendary ludruk